2019
DOI: 10.2174/1389200219666181026160242
|View full text |Cite
|
Sign up to set email alerts
|

Iron and Vitamin D/Calcium Deficiency after Gastric Bypass: Mechanisms Involved and Strategies to Improve Oral Supplement Disposition

Abstract: Background:Nutritional deficiencies are common following Roux-en-Y Gastric Bypass (RYGB). Aetiology is diverse; including non-compliance, altered diet, unresolved preoperative deficiency and differential degrees of post-operative malabsorption occurring as function of length of bypassed intestine. Iron and calcium/vitamin D deficiency occur in up to 50% of patients following RYGB. Currently, treatment strategies recommend the prescription of oral supplements for those who become deficient. Meanwhile, debate ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 87 publications
0
17
0
Order By: Relevance
“…Another limitation of this study is that the effect of the potentially altered 25-hydroxylation on vitamin D status cannot be well-studied in this model, as vitamin D deficiency is a common consequence of gastric bypass operation because of impaired gastric absorption. (34) It is currently unclear whether obesity-induced CYP2R1 repression in adipose tissue could contribute to the reduced plasma 25-OH-levels. Interestingly, according to the human tissue atlas, 20 CYP2R1 appears to be expressed rather ubiquitously in most tissues, and the liver expression is not particularly high among human tissues ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another limitation of this study is that the effect of the potentially altered 25-hydroxylation on vitamin D status cannot be well-studied in this model, as vitamin D deficiency is a common consequence of gastric bypass operation because of impaired gastric absorption. (34) It is currently unclear whether obesity-induced CYP2R1 repression in adipose tissue could contribute to the reduced plasma 25-OH-levels. Interestingly, according to the human tissue atlas, 20 CYP2R1 appears to be expressed rather ubiquitously in most tissues, and the liver expression is not particularly high among human tissues ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation of this study is that the effect of the potentially altered 25‐hydroxylation on vitamin D status cannot be well‐studied in this model, as vitamin D deficiency is a common consequence of gastric bypass operation because of impaired gastric absorption. ( 34 )…”
Section: Discussionmentioning
confidence: 99%
“…In a 2019 questionnaire-based survey on 533 BS patients, Mahawar et al showed that slightly over half of the respondents reported non-adherence to micronutrient supplementation [107]. The main micronutrient deficiencies reported after RYGB and VSG include vitamin B 12 , folic acid, iron, thiamine (vitamin B 1 ), vitamin D, and calcium [108][109][110][111][112]. Other reports on nutritional deficiencies after weight loss surgery, particularly following mixed bariatric procedures, are for fat liposoluble soluble vitamins, namely, vitamin A [113], vitamin E [114], and vitamin K [115], as well as for copper [116], zinc, and selenium [117,118].…”
Section: Pathogenesis Of Micronutrient Deficiencies After Bsmentioning
confidence: 99%
“…The impact of modification of the length of the standard RYGB alimentary limb should be investigated to determine if a shorter limb length can achieve comparable metabolic control and weight-independent renoprotective benefits while minimising hyperoxaluria risk to improve net renal outcomes. Additionally, nutritional deficiencies in iron, calcium, and vitamin D after metabolic surgery may exacerbate anaemia and mineral bone disease as complications of CKD (130). Oxalosis as a consequence of enteric hyperoxaluria may also result in erythopoeitin-stimulating agent resistant anaemia (131).…”
Section: Future Directionsmentioning
confidence: 99%